Влияние ориентации начальной трещины и контактного трения на разрушение хрупких тел - Костандов, Ю.А.; Медведев, В.С. (Геотехническая механика, 2012)
Проведено експериментальне дослідження особливостей руйнування зразків з початковою тріщиною при їх одноосному стискуванні. Встановлена залежність міцності таких зразків, утворення і розвитку магістральних тріщин від орієнтації початкової тріщини відносно навантажуваних граней зразка і величини контактного тертя на них. Запропоновано пояснення цієї залежності. The experimental research of fracture features of specimens with an initial crack at their axial compression is carried out. Dependences of strength such specimens, formation and development of main cracks from orientation of an initial crack relatively specimen bounds, which loaded by the uniaxial compression, and value of contact friction on them is set. The explanation of these dependences is offered.